Effect of Tylvalosin on Biochemical Parameters in Healthy Broiler Chickens - Ammar H.Salman; Mohammed Mosleh Shwaish; Asif Hasan Abdulrazaq (Institute of Medico-legal Publications Pvt Ltd, 2021)
To evaluate the effects of tylvlosin on biochemical parameters in broiler chicken, twenty broiler chicks(Ross 308) aged 21 days old and weight 600-800 gm was divided into two equal groups, the first one wascontrol group (G1) and the second one was treated group (G2). G1 dosed with 1ml/kg of body weight ofnormal saline while G2 dosed with 25mg/Kg of body weight of Tylvalosin. Blood samples were collectedwith plain tubes for serum collection after 4 days of treatment. The serum was used to evaluate ALT, AST,Alkaline phosphatase, Albumin and Urea, Uric acid, and total protein and bilirubin. The results showed asignificant increase in total bilirubin in G2 as compared with G1, while other parameters didn’t show anysignificant changes between the two groups.In conclusion, Tylvalosin can be used safely in chickens without affecting liver and kidney functions.